Pregnant Adolescent Girls' Dietary Habits and Status in Mali - Tambadou, Dr. Youssouf (American Journal of Food Sciences and Nutrition, 2023)
Purpose: The purpose of this study was to evaluate dietary habits and nutrition status of pregnant adolescents. Methodology: The study used a desktop literature review methodology (desk study). This required a thorough analysis of research on the dietary habits and nutrition status of pregnant adolescents. The subject of the study underwent three phases of sorting in order to assess its suitability for further study. Findings: This study concludes that the poor nutrition status was associated with inadequate dietary intake and frequent illness. The low knowledge was attributed to low education level and poor health seeking behavior. The low knowledge translated to poor decision making in dietary practices. Unique Contribution to Theory, Practice and Policy: This study recommends ministry of Health at National level to enhance the use of the existing training package and policy in counselling pregnant adolescents. It should also come up with a counselling package and policy for use in counselling these mothers.